Physical activity and lifestyle interventions for children at cardiovascular risk: A systematic review - Contreras-Zapata, Katherine Estephani; Martín Pérez, Sebastián Eustaquio; Cruz-Hidalgo, Nadia Ximena; Rubio Zarapuz, Alejandro; Clemente Suárez, Vicente Javier; Martín Pérez, Isidro Miguel (Annales Kinesiologiae, 2025)
Introduction: Structured physical activity and lifestyle changes are promising strategies to reduce cardiovascular risk in children and adolescents. We hypothesize that programs meeting the minimum thresholds of frequency and duration—particularly those combining aerobic and resistance components—can significantly lower the blood pressure in at-risk pediatric populations. Purpose: To synthesize current evidence on the effectiveness of aerobic, resistance, and combined exercise interventions, alongside lifestyle modifications, in reducing cardiovascular risk among children and adolescents. Methods: A systematic review was conducted following PRISMA guidelines (PROSPERO CRD42025644256). Searches covered January 2015 to March 2025 across MEDLINE (PubMed), SPORTDiscus (EBSCO), and the Cochrane Library. The included studies were RCTs or quasi-experimental designs integrating exercise with dietary or behavioral components. The primary outcomes were blood pressure, lipid profile, body composition, physical fitness, and health-related quality of life. Study quality was assessed using the PEDro scale and Cochrane RoB 2.0 tool. Results: Twenty-six studies (mean PEDro score: 9.9/10) met the inclusion criteria. Combined aerobic and resistance training with nutritional or behavioral support led to reductions in systolic/diastolic BP (–5 to –8 mmHg), body fat (–2 to –4%), and cholesterol (–10 to –15 mg/dL), alongside gains in aerobic capacity. Interventions involving families and school personnel showed greater adherence and cardiometabolic improvements. Conclusions: Integrated physical activity and lifestyle programs are effective at reducing cardiovascular risk markers in pediatric populations. Early implementation in supportive environments is essential for long-term health benefits.